급식소 위생관리 개선방안에 대한 급식소 관리자의 중요도 평가 - 배현주(Hyun Joo Bae); 이혜연(Hye Yeon Lee) (Korean journal of community nutrition, 2010)
The purposes of this study were to evaluate on the importance about the possible remedies for improvement of sanitation management by foodservice manager and to compare dietitians' opinion and that of administrators about theirs. A questionnaire survey was performed by 282 dietitians and 56 administrators, who were involved at foodservice facilities in Daegu and Gyeongbuk from March 7 to March 9 in 2007. According to the results of the importance evaluation analysis about the remedies for improvement of sanitation management, there were significant differences between dietitians and administrators in the means of 6 items such as "remodeling of hygiene equipment and facilities", "improvement of dietitians' food safety knowledge", "self-operated management of foodservice operation", "enforcement of cooperation between the CEO or administrators and dietitians", "development of food safety education program for foodservice workers", "increasing of foodservice operating budget". In all of them, the dietitians' evaluation scores were significantly higher than that of administrators. In addition, four factors were extracted by exploratory factor analysis. According to the results of one-way ANOVA, operating, education, and policy support sector showed that significant differences across type of foodservice, frequency of meals served, number of meals served per day, dietitians' education level and career. On the other hand, supervision sector showed that significant differences across number of meals served per day and dietitians' employment type. In conclusion, in order to increase the quality of sanitation in the foodservice operation, we should increase sanitation performance and enforce the food-safety education for foodservice workers. In addition, government should increase the policy support.